Myeloid-Derived Suppressor Cells Promote Metastasis in Breast Cancer After the Stress of Operative Removal of the Primary Cancer - Ma, Xuelei; Wang, Manni; Yin, Tao; Zhao, Yunuo; Wei, Xiawei (Frontiers in Oncology, 2019)
Objective: To investigate the role of myeloid-derived suppressor cells (MDSC) in cancer progression after the stress of operative removal and the potential treatment value of MDSC depletion. Summary Background Data: Surgery is the most important treatment strategy in breast cancer. Recent research has provided evidence that operations may promote cancer metastases under some circumstances. Methods: A mouse model of breast cancer (administration of the murine breast cancer 4T1 cells subcutaneously) and the stress of operation was used to compare immune responses and survival outcomes. Flow cytometry was performed to detect the expression of CD11b and Gr1 MDSCs in tumor tissues and lung metastases. Cytokine levels were detected with three-color flow cytometry and enzyme-linked immunosorbent assay (ELISA). MDSCs were isolated and co-cultured with 4T1 cells to identify any morphorlogical change with immunofluorescence. The anti Gr-1 antibody was used to detect the function of the anti-Gr1 treatment in breast cancer. Results: The operative stress impaired the overall survival, leading to an increased number of MDSCs that preferentially infiltrated the tumor microenvironment and promoted tumor metastasis. In both in vitro and in vivo assays, MDSCs induced the epithelial-mesenchymal transition (EMT) of tumor cells through the up-regulation of TGF-beta1, VEGF, and IL-10. Furthermore, a treatment strategy of MDSC depletion was found to reduce pulmonary metastases after operations. Conclusions: The stress of operation could impair the overall survival in mice. The infiltrated MDSCs appear to induce EMT of tumor cells and increase metastases through the up-regulation of TGF-beta1, VEGF, and IL-10 levels. MDSC depletion could be a promising treatment strategy to prevent immune evasion after operations.